The River Queen : a memoir - Morris, Mary, 1947- (Henry Holt, 2007)
In fall 2005 travel writer Mary Morris set off down the Mississippi in a battered old houseboat called the River Queen, with two river rats named Tom and Jerry--and a dog who hated her. It was a time of emotional turmoil for Morris: her father had just died; her daughter was leaving home; life was changing all around her. So she decided to return to the Midwest where she was from, to the river she remembered. Morris describes living like a pirate and surviving a tornado. Because of Katrina, oil prices, and drought, the river was often empty--a ghost river. As she learned to pilot her boat and made peace with her dog, Morris got her groove back, reconnecting to her past. More important, she came away with her best book.--From publisher description.